Traversable Finslerian wormholes supported by phantom energy - Singh, Ksh. Newton; Rahaman, Farook; Deb, Debabrata; Maurya, S. K. (Frontiers in Physics, 2023)
This paper supplements the article (Eur. Phys. J. C 76: 246, 2016) by extending some more new wormhole solutions in the background of Finslerian geometry. Here, we present six more solutions by considering i) a linear equation of state (EoS) pr = ωρ and three different shape functions, ii) a linear relationship between radial and tangential pressure as pt = npr with two different redshift functions and iii) a specific density profile with a linear equation of state pr = ωρ. It is found that all these wormholes are violating null energy condition (NEC) signifying that the throats are opened by exotic matters. Since the equation of state parameters, ω or ωr = pr/ρ for all the solutions are <−1, the corresponding exotic matter is none other than the phantom energy. Further, the two solutions in Case ii) are not asymptotically flat since limr→∞[b(r)/r]↛0. To make it asymptotically flat we matched it with the Schwarzschild vacuum.